Tratamento de efluente de curtume por biofiltro aerado Submerso pré-tratado com microfiltro de membrana - Bahia, Adilson Silva [UNESP] (2014)
The effluents from leather tanning process have in addition to high concentrations of organic matter in terms of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD), high concentrations of total solids, total suspended solids and sulfide, which makes problematic the treatment of these effluents. The objective of this study was to evaluate the biotreatability of tannery effluent by submerged aerated biofilter after microfiltration membrane pretreatment. The results showed that can be used in the technical feasibility of BF removal of organic sulphide and industrial raw tannery wastewater as it amounted, respectively, removal to 84% and 98%